(untitled) - Kinjo (New York, 1989)
This book is part of the Our Name in History series, a collection of fascinating facts and statistics, alongside short historical commentary, created to tell the story of previous generations who have shared this name. The information in this book is a compendium of research and data pulled from census records, military records, ships' logs, immigrant and port records, as well as other reputable sources
Keywords: Japan fiction,Japanese literature